Synthesis, Structure, Properties and Time-Dependent Density Functional Theory Calculations of Cadmium Complex - Chen, Wen-Tong; Hu, Rong-Hua; Yi, Xiu-Guang; Wang, Yin-Feng; Luo, Zhi-Gang; Fu, Hong-Ru; Liu, Juan; Chen, Hua-Long (Asian Journal of Chemistry, 2014)
A cadmium complex CdCl2(2,2'-bipy)2 (1) (bipy = bipyridine) was obtained by a hydrothermal reaction and structurally characterized by single-crystal X-ray diffraction. Photoluminescent study shows that complex 1 exhibits a greenish yellow emission. Theoretical investigations reveal that the emission is ascribed to the ligand-to-ligand charge transfer (LLCT). The spectral data of FT-IR were also reported.